Efficient functional screening of a cellular cDNA library to identify severe fever with thrombocytopenia syndrome virus entry factors - Shimojima, Masayuki; Sugimoto, Satoko; Taniguchi, Satoshi; Yoshikawa, Tomoki; Kurosu, Takeshi; Saijo, Masayuki (Scientific reports, 2020)
The identification of host cell factors for virus entry is useful for the molecular explanation of viral tropisms and often leads to a more profound understanding of virus-induced diseases. Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease caused by SFTS virus. No countermeasures against the disease exist. In this report, we show an efficient method using virus-like particles for the functional screening of a cellular cDNA library to identify SFTS virus entry factors. Two variants encoding dendritic cell-specific ICAM-3 grabbing non-integrin related (DC-SIGNR), a calcium-dependent lectin known to enhance SFTS virus infection, were successfully identified from a human liver cDNA library. We will discuss applications for yet unidentified factor(s) for SFTS virus entry and for entry factor(s) for other viruses related to SFTS virus.